Analysis of Teacher Empowerment and Professional Practices on Individual Innovation with Self Efficacy as an Intervening Variable - Eko Budi Saputro (Jurnal Manajemen, 2025)
This study is motivated by the importance of individual innovation among teachers to improve the quality of learning. The purpose of this study is to analyse the effect of Teacher Empowerment and Professional Practices on Individual Innovation with Self-Efficacy as an intervening variable. The study population included 111 public junior high school teachers in Purworejo District, Purworejo Regency, using the census method. Data analysis was carried out using the PLS-SEM method through SmartPLS 4 software. The results showed Teacher Empowerment had a positive but insignificant effect on Individual Innovation, but a significant positive effect on Self-Efficacy. Professional Practices proved to have a positive and significant effect on Individual Innovation and Self-Efficacy. In addition, Self-Efficacy has a positive and significant effect on Individual Innovation and acts as a significant mediator in the indirect relationship between variables.